Nutritional Status of Toddlers in Talang Babat Village, East Tanjung Jabung Regency - Enny Susilawati; Herinawati Herinawati; Lia Artikasari; Deliyana Fatilaya (STIKes Hang Tuah Pekanbaru, 2021)
Nutrition is a very important part of growth and development. Community problems are considered serious if the prevalence of underweight is between 10.0-14.0%, and is considered critical if it is greater than 15.0% (WHO, 2010). In 2013, nationally the prevalence of underweight in children under five was still 12.1%. For Jambi Province itself, cases of malnutrition tended to increase over the last two years, in 2017 there were 85 cases of malnutrition and four cases died, while in 2018 it rose to 92 cases with six of them died. This study is an analytical study with a cross-sectional design that aims to determine the relationship between diet and mother's knowledge with the nutritional status of children under five in Talang Babat Village, Tanjung Jabung Timur Regency in 2019. This research was conducted in July 2019. The population in this study was 220 toddlers. The number of samples was calculated based on Ariawan's formula as many as 67 people. The sampling technique was carried out by means of quota sampling. Data analysis used the chi-square test with a significant limit of = 5%. The results of the study Most of the respondents had normal nutritional status as many as 50 respondents (74.6%), had a good diet for toddlers as many as 37 respondents (55.2%) and had less knowledge about the nutritional status of toddlers as many as 43 respondents (64.2%). Based on the chi-square statistical test with p-values ​​of 0.028 and 0.001 which means there is a significant relationship between diet and knowledge with the nutritional status of children under five in Talang Babat Village, Tanjung Jabung Timur Regency. From the results of the study, it can be concluded that there is a significant relationship between diet and knowledge with the nutritional status of toddlers in Talang Babat Village, Tanjung Jabung Timur Regency.